2012
DOI: 10.1126/science.1213351
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Efflux Mediated by SWEET Proteins as a Key Step for Phloem Transport

Abstract: Plants transport fixed carbon predominantly as sucrose, which is produced in mesophyll cells and imported into phloem cells for translocation throughout the plant. It is not known how sucrose migrates from sites of synthesis in the mesophyll to the phloem, or which cells mediate efflux into the apoplasm as a prerequisite for phloem loading by the SUT sucrose-H(+) (proton) cotransporters. Using optical sucrose sensors, we identified a subfamily of SWEET sucrose efflux transporters. AtSWEET11 and 12 localize to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
1,245
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,116 publications
(1,389 citation statements)
references
References 52 publications
54
1,245
3
Order By: Relevance
“…Other studies have also found consistency in nectar sugar concentration between different varieties of OSR (Mohr & Jay, 1990; Mesquida et al ., 1991; Pierre et al ., 1996). While it is known that the family of SWEET protein transporters in plants, including brassicas, facilitate the diffusion of sucrose from photosynthetic to heterotrophic cells, such as nectaries, down a concentration gradient (Chen et al ., 2012; Chen, 2014; Lin et al ., 2014), little is known about the regulation of concentration in nectar sugar, and this is an emerging area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found consistency in nectar sugar concentration between different varieties of OSR (Mohr & Jay, 1990; Mesquida et al ., 1991; Pierre et al ., 1996). While it is known that the family of SWEET protein transporters in plants, including brassicas, facilitate the diffusion of sucrose from photosynthetic to heterotrophic cells, such as nectaries, down a concentration gradient (Chen et al ., 2012; Chen, 2014; Lin et al ., 2014), little is known about the regulation of concentration in nectar sugar, and this is an emerging area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate is transported as sucrose to sink tissues through the phloem. The key step for phloem loading is sucrose efflux, which is mediated by SWEET proteins (32). We determined that SWEET15/SAG29 is induced in senescing Arabidopsis leaves.…”
Section: Phosphorylation Of Abfs By Snrk2s Facilitates Aba-induced Sag12mentioning
confidence: 98%
“…The functions of transporting glucose and sucrose are identified in most well-studied SWEETs currently (Chen et al 2010;Chen et al 2012). For example, AtSWEET1 is involved in the regulation of glucose uptake and efflux (Chen et al 2010;Sonnewald 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, AtSWEET1 is involved in the regulation of glucose uptake and efflux (Chen et al 2010;Sonnewald 2011). OsSWEET11 and OsSWEET14 are the low affinity transport sucrose carriers that may be involved in the phloem sucrose loading process (Chen et al 2012;Chen 2014). AtSWEET1/4/5 may directly involve in the transport of sugar to regulate the osmotic active substances, or participate in cell wall sugar loading (Bauer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation